2008
DOI: 10.1111/j.1399-302x.2008.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Sugar fermentation in probiotic bacteria – an in vitro study

Abstract: The metabolic capacity to form acid from dietary sugars differed significantly between the various probiotic strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 27 publications
(33 reference statements)
11
76
1
2
Order By: Relevance
“…The fruiting body of button mushrooms also contains fructose (0.62-6.02 mg/g dry matter), lactose (0-3.8 mg/g dry matter), sucrose (0.41-1.48 mg/g dry matter), and trehalose (0.88-5.31 mg/g dry matter). Additionally, lactic acid bacteria, including probiotic strains, exhibit varied degrees of the utilisation of these carbon sources (Hedberg et al, 2008). Available sources recommend the addition of sugar in the fermentation process (Jabłońska-Ryś and Sławińska, 2012;Jabłońska-Ryś et al, 2005;Joshi et al, 1996;Mering, 1955;Milanovič et al, 2010;Niksic et al, 1997;Skąpska et al 2008;Stojanovic et al, 1994); only Kreß and Lelley (1991) carried out lactic fermentation of mushrooms without the addition of sugar.…”
Section: Introductionmentioning
confidence: 99%
“…The fruiting body of button mushrooms also contains fructose (0.62-6.02 mg/g dry matter), lactose (0-3.8 mg/g dry matter), sucrose (0.41-1.48 mg/g dry matter), and trehalose (0.88-5.31 mg/g dry matter). Additionally, lactic acid bacteria, including probiotic strains, exhibit varied degrees of the utilisation of these carbon sources (Hedberg et al, 2008). Available sources recommend the addition of sugar in the fermentation process (Jabłońska-Ryś and Sławińska, 2012;Jabłońska-Ryś et al, 2005;Joshi et al, 1996;Mering, 1955;Milanovič et al, 2010;Niksic et al, 1997;Skąpska et al 2008;Stojanovic et al, 1994); only Kreß and Lelley (1991) carried out lactic fermentation of mushrooms without the addition of sugar.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast Keller and Twetman found no evidence for an increased plaque acidity for L. plantarum 299 v with fructose or xylitol [37]. Strains with low metabolic activity are favourable, for example L. paracasei [38].…”
Section: Strain Selectionmentioning
confidence: 92%
“…Tolerability of lactobacilli based probiotics has been demonstrated [12][13][14][15] and compliance of 75-85% has been observed [1,15] in studies of bacterial pathogens Furthermore, a two-year trial on the effects of VSL#3 on C. difficile associated diarrhea showed the probiotic was well tolerated though issues with adherence occurred, for reasons similar to our findings [15]. In a recent trial examining the acceptability and tolerance of probiotics for patients with carriage by Methicillinresistant Staphylococcus aureus, we found that the chosen probiotic (L. rhamnosus HN001) was well tolerated [16].…”
Section: Discussionmentioning
confidence: 99%